STRUCTURAL ANALYSIS OF SUPRAMOLECULAR COMPLEXES OF SCHIFF BASES - Khakberdiyev Shukhrat Mahramovich, Mamatova Farangiz Qodir qizi, Azizova Safina Isroiljon qizi (Journals Park Publishing, 2023)
Gossypol Schiff bases were synthesized and water-soluble supramolecular complexes of monoammonium salt of glycyrrhizic acid (MSGA) in a ratio of 1:4 were obtained, taking into account the insolubility of these substances in water. Some physico-chemical parameters of the complexes, their structure were estimated using IR-, UV-spectra and computer software. These quantum-chemical calculations were carried out in the ChemOffice program using the molecular mechanics (MM2) method with an empirical force field.
Keywords: Gossypol, amino compound, Schiff's base, spectrum, polyphenol, triterpene, aldehyde, cotton plant, naphthalene, MSGA.